New Product Development Strategy and its Impact on MSME Growth: A Bibliometric Analysis - Judijanto, Loso; Febriyanto, Weda; Supriandi, Supriandi (West Science Interdisciplinary Studies, 2024)
This study provides a comprehensive analysis of the research landscape surrounding New Product Development (NPD) strategies and their impact on the growth of Micro, Small, and Medium Enterprises (MSMEs). Through a bibliometric analysis using VOSviewer, key themes and trends were identified, including the centrality of SME growth, the critical role of finance and government policy, the importance of resilience in response to external shocks like COVID-19, and the strategic focus on marketing and competitive advantage. The findings suggest that tailored financial products, supportive government policies, and an emphasis on digital transformation are essential for enhancing SME growth. Additionally, fostering an innovative and customer-oriented business culture is crucial for maintaining a competitive edge. These insights provide practical implications for policymakers, business leaders, and financial institutions, emphasizing the need for a comprehensive approach to supporting SME development in dynamic market environments.